2018
DOI: 10.5946/ce.2017.059
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Percutaneous Endoscopic Gastrostomy Tubes in Centenarian Patients

Abstract: Background/AimsPercutaneous endoscopic gastrostomy (PEG) is a relatively safe procedure; however, no study has evaluated the safety of PEG tube placement in patients over the age of 100 years. MethodsWe conducted a retrospective review of patient records for patients who underwent PEG tube placement. Thirty patients aged 100 years and older were identified and a random sample of 275 patients was selected for comparison. ResultsThe mean age of the patients was 80.6±16.2 years. No procedure-related deaths or maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
5
2
Order By: Relevance
“…In another study, significant correlations were found between serious complications requiring a PEG tube change and mortality rates (13). Unlike this publication, no significant correlations were found between complications rates and mortality rates in this study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In another study, significant correlations were found between serious complications requiring a PEG tube change and mortality rates (13). Unlike this publication, no significant correlations were found between complications rates and mortality rates in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…On the contrary, reduced PEG-related mortality rates have been reported from studies in patients experiencing dysphagia as a result of amyotrophic lateral sclerosis or stroke (12). In a publication, Young et al reported lower 30-day mortality rates in patients who underwent a PEG tube placement procedure due to dysphagia associated with neurological disorders, including Parkinson's disease and stroke (13). In our study, no death occured within 30 days after the procedure.…”
Section: Discussioncontrasting
confidence: 62%
“…Centenarians, however, have traditionally been excluded from intervention trials. The evidence-based practice for caring of this population has just begun to be established, showing different treatment responses and adverse event profiles (Sobani et al, 2018;Tapia Rico et al, 2018). Findings from this study support the heterogeneity in ADL independence and a multipronged approach to address ADL independence is critical.…”
Section: Relevance For Clinical Practicementioning
confidence: 53%
“…Dong-jun Oh's (29) study of patients older than 65 years found no difference in mortality and procedure-related complications compared to those of younger patients. Sobani Zan and colleagues (35) studying patients over 100 years of age found no differences regarding the serious complications, success rate or patient mortality associated with PEG tubes and concluded that PEG tube can be administered with careful selection in patients older than 100 years.…”
Section: Discussionmentioning
confidence: 99%